2008
DOI: 10.1007/s00167-008-0528-8
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-hydroxyapatite composite versus polymer interference screws in anterior cruciate ligament reconstruction in a large animal model

Abstract: The aim of the study was to assess the hard tissue response of a composite hydroxyapatite/poly L-lactic acid (HA/PLLA) interference screw for anterior cruciate ligament (ACL) reconstruction compared to a standard PLLA screw. Twelve skeletally mature rams underwent unilateral ACL reconstruction using an autologous bone-patellar tendon graft. Each animal received either two test HA/PLLA interference screws or two control PLLA interference screws. Animals were sacrificed at 6 and 12 months post-implantation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…131 In addition, Hunt et al demonstrated significantly more new bone formation and decreased inflammatory response when comparing composite HAP/PLLA interference screws to PLLA screws in a large animal ACL reconstruction model. 132 Likewise, PLGA scaffolds coated with CaP resulted in a significantly lower inflammatory response, as determined by histomorphometrical analysis of FBGCs, in comparison to non-coated PLGA scaffolds at 8-weeks post-implantation. 133 Thus, through the incorporation or coating of implants with biomimetic agents, increased bone regeneration and decreased FBR may be attained.…”
Section: Efforts To Mitigate Fbrmentioning
confidence: 91%
“…131 In addition, Hunt et al demonstrated significantly more new bone formation and decreased inflammatory response when comparing composite HAP/PLLA interference screws to PLLA screws in a large animal ACL reconstruction model. 132 Likewise, PLGA scaffolds coated with CaP resulted in a significantly lower inflammatory response, as determined by histomorphometrical analysis of FBGCs, in comparison to non-coated PLGA scaffolds at 8-weeks post-implantation. 133 Thus, through the incorporation or coating of implants with biomimetic agents, increased bone regeneration and decreased FBR may be attained.…”
Section: Efforts To Mitigate Fbrmentioning
confidence: 91%
“…Also, incorporation of HA into PLLA enhances protein adsorption and increases the compressive modulus in comparison with pure PLLA scaffolds [24] . In one study, mouse fibroblasts cultured on PLLA/HA scaffolds showed a reduction in the inflammatory response compared with pure PLLA [25] . The stress-shielding problem is a result of elastic modulus mismatch between metallic materials and natural bone.…”
Section: Introductionmentioning
confidence: 99%
“…PLA is used extensively in surgery as suture materials and bone fixation devices; a large number of investigations have been carried out on PLA and its copolymers in biomedical applications for resorbable medical implants [6–8]. Biodegradable polymers like PLA have specific advantages over metallic or ceramic materials in medical applications [9,10]. PLA can be used in the shape of a rod, plate, screw, fiber, sheet, sponge, or beads for bone and tissue engineering, or as microspheres for drug delivery systems [3,11].…”
Section: Introductionmentioning
confidence: 99%